ПОМОШНИОТ ГЛАГОЛ сум ВО МАКЕДОНСКИОТ ЈАЗИК И ПОМОШНИОТ ГЛАГОЛ i- ВО ТУРСКИОТ ЈАЗИК - Marija Leontić (Philological Studies, 2019)
Both Macedonian and Turkish have specific characteristics of grammar, but they also have simular items. Macedonian and Turkish have the verb to be (Macedonian сум, Turkish i-) with similar function in both languages. In Macedonian, there are: present tense, past tense, future tense and posibilitive of to be. In Turkish there are: present, past, reported and the conditional form of to be. This paper will examine the verb to be (Macedonian сум, Turkish i-) and their uses with nouns in Macedonian and Turkish, respectively.